5-fluorouracil encapsulated CS-mPEG nanogels for controlling drug release - Hai, Nguyen Dai (Vietnam Journal of Chemistry, 2017)
The purpose of this study is to synthesize and characterize poly (ethylene glycol) methyl ether (mPEG) conjugated chitosan (CS), mPEG-CS, at different ratios of 5-Fluorouracil (5-FU) delivery (5-FU-loaded mPEG-CS). The chemical cross-linking of these polymers were prepared by using 4-Nitrophenyl chloroformate reagent. The obtained mPEG-CS was characterized by Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (1H NMR) spectroscopy. The 5-FU-loaded mPEG-CS particles were nearly spherical in shape with a mean diameter of 61.25 nm, determined by transmission electron microscopy (TEM). In addition, the entrapment efficiency of 5-FU was approximately 10 %. Whereas the encapsulation efficiency and loading capacity were independent of different molar ratios of mPEG, there was one factor that particularly stands out, which is 5-FU release behavior. These results indicated that mPEG-CS nanogels present the potential for controlled release of 5-FU working as a delivery system in cancer therapy. Keywords. Poly(ethylene glycol) methyl ether, chitosan, 5-fluorouracil, nanogels, drug delivery system.